SNCA rs3910105 Is Associated With Development of Rapid Eye Movement Sleep Behavior Disorder in Parkinson’s Disease - Yang, Nan-nan; Sang, Shu-shan; Peng, Tao; lu, Hong (Frontiers in Neuroscience, 2022)
Background and Purpose: Rapid eye movement (REM) sleep behavior disorder (RBD) is a common nonmotor symptom of PD. However, the association between the SNCA rs3910105 genotype and rapid eye movement (REM) sleep behavior disorder (RBD) in Parkinson’s disease (PD) remains unclear. Methods: This study used Parkinson’s Progression Markers Initiative (PPMI) data and included 270 patients with newly diagnosed PD without RBD who were divided into SNCA rs3910105 C carriers (CC+CT; n= 187) and TT carriers (n = 83). They were followed up for 5 years to identify the development of RBD. To investigate the influence of cerebrospinal fluid (CSF) alpha-synuclein (α-syn) and β-amyloid 1–42 (Aβ42) in the association between rs3910105 and RBD, the patients were additionally classified into “high-level” and “low-level” groups using cutoff values for CSF α-syn and Aβ42 levels. Results: At baseline, the rs3910105 C allele group had lower CSF α-syn and Aβ42 levels than the TT group. During the 5.0-year follow-up, the rs3910105 C allele group had a higher incidence of RBD than the TT group. In the subgroup analyses, the effect of the rs3910105 C allele was not found in the “low-level” group. However, in the “high-level” group, the rs3910105 C allele independently increased the risk of RBD. Conclusions: The SNCA rs3910105 C allele might be a novel genetic risk factor for RBD development in PD. This association seemed to be mainly mediated by an α-syn-dependent pathway.